Empowerment relationship in intra organization entrepreneurship - Morteza Shahbakhsh; Negar Elhamian; Hassah Shahraki Pour (Dutch Journal of Finance and Management, 2019)
The current research was done with the goal of investigating the relationship between human resources empowerment dimension and the employees of Zabol University of medical sciences entrepreneurial level. The method of research is survey descriptive and the research statistical population includes all employees of Zabol University of medical sciences in 2014 that were 270 people that considering Morgan table 155 people were chosen as sample. Sampling method was random simple. Research tools is research made questionnaire including 30 questions that its validity were confirmed by experts , teachers and Guide Master and its Cronbach's alpha coefficient reliability was calculated as 0.779. For data statistical analysis descriptive statistical indexes, mean, standard deviation and statistic and single sample t test and factor analysis were used for analyzing research questions which were done using software SPSS and Amos on data. The result of test showed that there is a relationship between empowerment with the employees of Zabol University of medical sciences entrepreneurial level. There is also relationship between empowerment dimensions mean self-effectiveness, autonomy, personal acceptance and trust with Zabol University of medical sciences entrepreneurial level.
Keywords: 650; entrepreneurship; empowerment; Zabol University of Medical Sciences